Organizational development as a modern management tool for transformation of the company (case of Ukrainian energy company) = Rozwój organizacyjny jako nowoczesne narzędzie zarządzania transformacją firmy (na przykładzie firmy energetycznej Ukrainy) - Doroshuk, Hanna (Zielona Góra: Faculty of Economics and Management Press)
Organizational development as a modern management tool for transformation the company (case of Ukrainian energy company) The article is aimed at formation of the approaches and stages of organizational development for a large vertically integrated company, ensuring the country's strategic security in the field of energy. The methodological basis of this work is the theory of the company's life cycle, and it is proposed to complement the mentioned theory with the theory of spiral dynamics, reflecting the evolution of the company's values.
Keywords: rozwój organizacyjny; zarządzanie zmianami; wartości firmy; strategiczne bezpieczeństwo kraju; przekształcenie; firma energetyczna; organizational development; change management; company value; country's strategic security; transformation; energy company